Extrajudicial Killing: Pelanggaran Hak atas Hidup dan Kaitannya dengan Asas Praduga Tak Bersalah - Alya Salsabila Munir; Bella Eka Saputri; Salsabila Azaria Rachma (CV Rewang Rencang, 2022)
Extrajudicial killings is an execution by state actor without judicial proceeding. Police officers as state actor in their duty enforcing the law have the authority to use firearms. However, there are police officers commit extrajudicial killings in their duties. Extrajudicial killing is a violation of the right of life that cannot be reduced under any circumstances and violation of the Presumption of Innocence. The results of this study showed that extrajudicial killing is extraordinary crime that has been regulated in national and international regulations. The responsibilty of extrajudicial killing is the state's obligation to protect the human rights of its citizens.